Pengaruh Kualitas Produk, Lokasi, dan Persepsi Harga Terhadap Keputusan Pembelian di Angkringan Iwan Cipinang - Affandy Dwinanto; Chatarina Yunita (LPPM Universitas Asa Indonesia, 2022)
The purpose of this research to determine and analyze the effect of product quality, location, price perception, and purchase decision of Warung Angkringan Iwan Cipinang. The population in this research was 100 respondents with data collection using a questionnaire given to respondents with accidental sampling technique. The analytical method used in this research is multiple regression analysis. The results of this research indicate that product quality variable, location variable, price perception variable simultaneously affect the purchasing decision of Warung Angkringan Iwan Cipinang. Then the results partially show that location and price perception variables have a significant effect on purchasing decision, while quality product variable have no effect on purchasing decisions.